2002
DOI: 10.1152/ajpheart.00031.2002
|View full text |Cite
|
Sign up to set email alerts
|

ADP-induced pial arteriolar dilation in ovariectomized rats involves gap junctional communication

Abstract: It was previously shown that, despite the loss of nitric oxide (NO) dependence, ADP-induced pial arteriolar dilation was not attenuated in estrogen-depleted [i.e., ovariectomized (Ovx)] rats. Additional evidence suggested that the NO was replaced by an endothelium-dependent hyperpolarizing factor (EDHF)-like mechanism. To further characterize the nascent EDHF role in Ovx females, the current study was undertaken to test whether, in Ovx rats, ADP-induced pial arteriolar dilation retained its endothelial depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
48
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 37 publications
8
48
1
Order By: Relevance
“…Myoendothelial gap junctions occur in greater density in resistance compared with conduit arteries and, consequently, it has been suggested that the gap junctions may play a role in the hormonal modulation of vascular relaxation (as an EDHF candidate). Indeed, it has been proposed that a decrease in the vascular expression of Cx43 alone or concomitantly with Cx40 could afford the reduction in EDHF-mediated responses in rat mesenteric arteries of ovariectomized rats , Xu et al 2002, Nawate et al 2005; this was substantiated by the observation that when animals were treated with 17b-estradiol, all responses were normalized (Chataigneau & Schini-Kerth 2005, Nawate et al 2005. In addition, it has been suggested that the increased EDHFmediated relaxation, associated with pregnancy in rats and humans (Pascoal & Umans 1996, Gerber et al 1998, Kenny et al 2002, is in part due to enhanced gap junctional communication at least in response to bradykinin in subcutaneous small arteries of pregnant women (Luksha et al 2004, Lang et al 2007).…”
Section: Edhfmentioning
confidence: 99%
“…Myoendothelial gap junctions occur in greater density in resistance compared with conduit arteries and, consequently, it has been suggested that the gap junctions may play a role in the hormonal modulation of vascular relaxation (as an EDHF candidate). Indeed, it has been proposed that a decrease in the vascular expression of Cx43 alone or concomitantly with Cx40 could afford the reduction in EDHF-mediated responses in rat mesenteric arteries of ovariectomized rats , Xu et al 2002, Nawate et al 2005; this was substantiated by the observation that when animals were treated with 17b-estradiol, all responses were normalized (Chataigneau & Schini-Kerth 2005, Nawate et al 2005. In addition, it has been suggested that the increased EDHFmediated relaxation, associated with pregnancy in rats and humans (Pascoal & Umans 1996, Gerber et al 1998, Kenny et al 2002, is in part due to enhanced gap junctional communication at least in response to bradykinin in subcutaneous small arteries of pregnant women (Luksha et al 2004, Lang et al 2007).…”
Section: Edhfmentioning
confidence: 99%
“…Indeed, there is evidence hinting at a link between estrogen and EDHF activity. EDHF-mediated responses to ACh, 9,27 shear stress, 28 ADP, 29 or Ca 2ϩ ionophore 30 are all reduced by ovariectomy; however, E2 is known to target several signal transduction pathways in the vasculature, including the muscarinic receptor M2 and M3 pathways, 31 which suggests that alternative mechanisms may be responsible at least for the changes in EDHF activity in response to ACh. It is unlikely that this latter mechanism is at play in the present study, because BK also produced relaxation of dKO arteries that persisted in the presence of NOS and COX inhibition, which demonstrates that EDHFmediated relaxation is a general phenomenon of these arteries and is not due to an increase in sensitivity to ACh.…”
Section: Male Mice Exhibit Dramatically Less Edhf Activity Than Femalmentioning
confidence: 99%
“…To that end, we determined whether injury of the GL [via topical exposure to the purported gliotoxin L-␣-aminoadipic acid (L-␣AAA)] alters hypercapnia-induced pial arteriolar dilation. On the basis of previous findings from our laboratory (40) showing that the gap junctional protein connexin43 (Cx43) is abundantly expressed in the GL, we postulated that Cx43-dependent gap junctional communication might serve to facilitate the spread of vasodilating signals along the GL, resulting in a more "global" influence on pial vessels. Thus we evaluated CO 2 reactivity in rats where GL Cx43 expression was knocked down using an antisense oligodeoxynucleotide (ODN) strategy (40).…”
mentioning
confidence: 96%
“…On the basis of previous findings from our laboratory (40) showing that the gap junctional protein connexin43 (Cx43) is abundantly expressed in the GL, we postulated that Cx43-dependent gap junctional communication might serve to facilitate the spread of vasodilating signals along the GL, resulting in a more "global" influence on pial vessels. Thus we evaluated CO 2 reactivity in rats where GL Cx43 expression was knocked down using an antisense oligodeoxynucleotide (ODN) strategy (40). In addition, previous studies have indicated that isocapnic local reductions in pH can dilate cerebral vessels in vivo and in vitro (2,14,16,32).…”
mentioning
confidence: 96%